Address in English from the standpoint of pragmalinguistics, sociolinguistics and psycholinguistics. - Keldiyorova, Marjona; Burieva, Nargiza (Журнал иностранных языков и лингвистики, 2023)
The turn of modern linguistics to the study of speech activity inevitably raised the question of the conditions for the success of its implementation, the methods of transmitting the message to the recipient in the most complete and undistorted form, and the means of influencing the addressee. The orientation of a speech towards the addressee is one of its main characteristics. Speech target is a universal category and it has an extensive arsenal of means of expression, both verbal and non-verbal. The main means of expressing the category of address is traditionally considered to be address, the complexity and functional duality of which constantly attracts the attention of linguists. The article studies the address in English language from the standpoint of pragmalinguistics, sociolinguistics and psycholinguistics. The relevance of the research is determined by the problems of the culture of speech, to which linguistics currently pays great attention.